The linear combination method is the same as the elimination method. Let's multiply the second equation by -2 so the x terms cancel each other out. When we do that we get a system of
![2x-3y=13](https://tex.z-dn.net/?f=2x-3y%3D13)
and
![-2x-4y=8](https://tex.z-dn.net/?f=-2x-4y%3D8)
. The x-terms cancel each other out giving us
![-7y=21](https://tex.z-dn.net/?f=-7y%3D21)
and y = -3. Now sub -3 into one of the equations to solve for x. x+2(-3)=-4, and x - 6 = -4. x = 2. So the solution for our system is (2, -3)
Answer:
A) Commutative
Step-by-step explanation:
The Associative has to do with re-grouping numbers. There are only two numbers so this does not apply here. Commutative is where you change the order; that's what the equation is demonstrating.
I think it’s d for the standard equation
Answer:
Where’s the picture
Step-by-step explanation:
formula is lsquare so answer is 25ft